2017
DOI: 10.1111/1462-2920.13923
|View full text |Cite
|
Sign up to set email alerts
|

High resolution visualization and exo‐proteomics reveal the physiological role of XlnR and AraR in plant biomass colonization and degradation by Aspergillus niger

Abstract: In A. niger, two transcription factors, AraR and XlnR, regulate the production of enzymes involved in degradation of arabinoxylan and catabolism of the released l-arabinose and d-xylose. Deletion of both araR and xlnR in leads to reduced production of (hemi)cellulolytic enzymes and reduced growth on arabinan, arabinogalactan and xylan. In this study, we investigated the colonization and degradation of wheat bran by the A. niger reference strain CBS 137562 and araR/xlnR regulatory mutants using high-resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The phenotype and exoproteome of the A. niger Δ xlnR mutant confirmed previous studies that reported impaired growth on cellulose, (arabino)xylan and xyloglucan (van Peij et al ., 1998a; Gruben et al ., 2017). Enzyme activity assays and proteomic studies also demonstrate the key role of XlnR in the utilization of (arabino)xylan and cellulose when grown on wheat bran, and correlate with a previous study that showed that colonization of wheat bran is mainly dependent on XlnR (Kowalczyk et al ., 2017a). However, it cannot be excluded that the phenotype of Δ xlnR includes reduced production of ClrA and ClrB targets, as it has previously been shown that XlnR affects the expression of the genes encoding these two transcription factors (Raulo et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype and exoproteome of the A. niger Δ xlnR mutant confirmed previous studies that reported impaired growth on cellulose, (arabino)xylan and xyloglucan (van Peij et al ., 1998a; Gruben et al ., 2017). Enzyme activity assays and proteomic studies also demonstrate the key role of XlnR in the utilization of (arabino)xylan and cellulose when grown on wheat bran, and correlate with a previous study that showed that colonization of wheat bran is mainly dependent on XlnR (Kowalczyk et al ., 2017a). However, it cannot be excluded that the phenotype of Δ xlnR includes reduced production of ClrA and ClrB targets, as it has previously been shown that XlnR affects the expression of the genes encoding these two transcription factors (Raulo et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The digestion was quenched with a solution of trifluoroacetic acid (1%) before flash freezing and storing at −80°C. The salts and detergents were removed using SCX SPE as described in Kowalczyk and colleagues () and the final peptide concentration was determined using a BCA assay to ensure the samples were diluted to 0.1 μg·μl −1 for LC–MS/MS processing.…”
Section: Methodsmentioning
confidence: 99%
“…the development of helium ion microscopy (HIM) led to an increase in imaging resolution and depth of field compared to scanning electron microscopy (SEM) (Joens et al, 2013). Using HIM, it was shown how A. niger hyphae colonised better on the "rough" compared to on the "smooth" surface of wheat bran (Kowalczyk et al, 2017). Also, HIM visualised the progressive degradation of lignocellulose over time, such as the thinning of cell wall structures in wood colonised by the white-rot D. squalens (Daly et al, 2018).…”
Section: Techniques and Insights For Visualising Fungal Lignocellulos...mentioning
confidence: 99%